EVALUATING CRP AND SOME HEMATOLOGICAL PARAMETERS IN COVID-19 PATIENTS IN THI–QAR PROVINCE (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2) appeared in the city of Wuhan, China at the end of 2019, which named COVID-19. In the present study we collected 50 samples from COVID-19 patients those who attend the Respiratory Diseases Center in Dhi Qar Governorate\ South of Iraq. The current study aimed to find out the concentration of C-reactive protein in the group of patients, and we also wanted to show the changes in the complete blood count reading that occurred in the patients. Where the obtained results were compared with 50 samples taken from apparently healthy people as a control group. Patients were diagnosed based on the clinical features, computed tomography of the lungs, nasopharyngeal swab samples and antibody testing IgG, IgM. After analyzing the results, high levels of CRP were found in the patients group, which was (40.2864) when compared with the control group (4.7857). White blood cells tends to be somewhat low compared to its normal values when the mean of it in patients group was (4.6),while in control group the mean of it was (8.8). The level of lymphocyte was decreased in patients group, where the result was significant where p= .012179.The mean of lymphocyte in patients group was0.76 ,while in control group was 3.9. Neutrophil mean was analogous in tow studied group. The mean of eosinophil was low in patients group (0.42) when we compared it with control group (5.00), as the p-value= .002504 .Hematocrit result was low in patients group was (33.2) than in healthy group was(51),as p value was < .00001 .The result of current study also exhibited that level of Red blood cells was analogous in two studied groups where it appears in normal range in patients group(4.25) and in control group.